Risk and safety assessment of hydrogen pipelines and storage tanks using preliminary hazard analysis - Asante-Okyere, Solomon; Mensah, Rhoda Afriyie; Sandström, Joakim; Försth, Michael (Frontiers in Chemical Engineering, 2025)
The safe operation of hydrogen pipelines and storage tanks is essential for the development of a sustainable hydrogen economy. However, these systems are exposed to significant risks that must be effectively managed to prevent hazardous outcomes. The present study therefore assessed the hazards and risks associated with hydrogen transport through pipelines and storage in tanks using the preliminary hazard analysis (PreHA) on the Hydrogen Incident and Accident Database (HIAD2.1), developed as part of the European Network of Excellence, HySafe. This database reports 34 accidents involving pipelines and 28 accidents involving storage tanks over the past 5 decades. The outcomes of these incidents vary, as majority of pipeline incidents led to fires, whereas storage tank failures were more likely to escalate into explosions. Other reported consequences in both pipeline and storage tanks included leaks with no ignition and near misses which are incidents that did not cause harm but had the potential to escalate into serious accidents. The PreHA analysis further identified corrosion and welding related issues as the main hazards for pipelines, while storage tanks were more often affected by operational failures as well as corrosion. Less frequent but high-impact event of natural disasters also posed catastrophic risks to both systems. Specific to pipeline integrity, it was observed that civil/construction work had a rare but notable impact. The findings of this study provide insights into the critical vulnerabilities of hydrogen pipelines and storage tanks and highlight the need for continuous improvement in safety management practices.